Yinma Jiedu granules combined with antibacterial drugs for patients with community-acquired pneumonia: protocol for a multicenter, randomized, double-blind, placebo-parallel controlled clinical trial - Li, Yuewei; Xiao, Jingmin; Fan, Feiting; Lin, Luoqi; Chi, Yihe; Tan, Xinyuan; Zhao, Wenhan; Wang, Weiliang; Zhou, Lizhi; Cao, Yinshu; Wu, Lei; Lin, Lin; et al. (Frontiers in Medicine, 2025)
BackgroundCommunity-acquired pneumonia (CAP) is a severe respiratory infection that can lead to a range of health issues. Yinma Jiedu (YMJD) granules, a representative classic traditional Chinese patent medicine, are widely used in China, yet high-quality evidence regarding their efficacy in alleviating clinical symptoms remains limited. This study aims to evaluate the efficacy and safety of YMJD granules for the treatment of CAP.MethodsThis multicenter, randomized, double-blind, placebo-controlled parallel clinical trial will be conducted at 11 hospitals in China, with each center enrolling patients competitively. A total of 226 CAP patients who meet the inclusion criteria will be stratified by age and then randomized in a 1:1 ratio to the intervention group (n = 113; YMJD granules) or control group (n = 113; YMJD placebo). All patients will receive a 7-day treatment course followed by a 7-day follow-up for assessment. The primary outcome is the clinical symptom improvement rate on day 4. Secondary outcomes include the clinical cure rate, the improvement rate of individual symptoms, the Cough and Sputum Assessment Questionnaire, the improved pneumonia imaging absorption evaluation scale, the CURB-65 score, the dosage and course of antibiotics, the changes in inflammatory markers, Traditional Chinese Medicine (TCM) syndrome scores and the amount of emergency drug used. Adverse events will also be assessed. Subgroup analyses will explore heterogeneity in YMJD treatment effects.DiscussionThis trial is the first large-sample, randomized, double-blinded, placebo-controlled study of YMJD granules in patients for CAP. It aims to elucidate the mechanisms of early symptoms improvement, identify optimal patient populations, and informing new therapeutic strategies.Ethics and disseminationThis study design was approved by the Ethics Committee of Guangdong Provincial Hospital of Chinese Medicine (Reference Number: BF2022-306-01).Clinical trial registrationhttps://www.chictr.org.cn/showproj.html?proj=189230, Identifier ChiCTR2300072343.